2012
DOI: 10.1080/10256016.2012.641543
|View full text |Cite
|
Sign up to set email alerts
|

Measuring nitrification in sediments – comparison of two techniques and three15NO measurement methods

Abstract: Nitrification is a crucial process in sediment nitrogen cycling. We compared two (15)N tracer-based nitrification measurement techniques (isotope pairing technique (IPT) combined with (15)N nitrate pool dilution and (15)N ammonium oxidation) and three different (15)N analyses from bottom water nitrate (ammonia diffusion, denitrifier and SPINMAS) in a sediment mesocosm. The (15)N nitrate pool dilution technique combined with IPT can be used to quantify the in situ nitrification, but the minimum detection limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 48 publications
4
25
0
Order By: Relevance
“…This corresponds to results of a comparison study where the SPIN–MAS method was compared with the diffusion method and the denitrifier method for 15 N analyses in nitrate from bottom water of a sediment mesocosm experiment. It was found that for 15 N-enriched samples the SPIN–MAS and denitrifier method gave similar results but that the diffusion method was not suitable for bottom water 15 N nitrate analysis probably due to cross-contamination . This backs up our finding that the SPIN–MIMS method, relying on the same chemical reactions as the SPIN–MAS method, is precise enough to analyze samples from enrichment studies even at low enrichment levels, and measurements are much faster and more convenient than all off-line methods.…”
Section: Discussionmentioning
confidence: 95%
“…This corresponds to results of a comparison study where the SPIN–MAS method was compared with the diffusion method and the denitrifier method for 15 N analyses in nitrate from bottom water of a sediment mesocosm experiment. It was found that for 15 N-enriched samples the SPIN–MAS and denitrifier method gave similar results but that the diffusion method was not suitable for bottom water 15 N nitrate analysis probably due to cross-contamination . This backs up our finding that the SPIN–MIMS method, relying on the same chemical reactions as the SPIN–MAS method, is precise enough to analyze samples from enrichment studies even at low enrichment levels, and measurements are much faster and more convenient than all off-line methods.…”
Section: Discussionmentioning
confidence: 95%
“…The analyses were determined using the denitrifier method (Sigman et al, 2001) at Appalachian Lab, University of Maryland. Potential nitrification rates were calculated based on the [ 15 N] fractional change (R 15 14 N) after 2 h of incubation, and the [NO 3 − ] and [NO 2 − ] existent at the same period, using the equation described by Jantti et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…In many benthic environments, particularly those with low bottom water NO 3 − , denitrification rates have been shown to be coupled to nitrification, which in turn is controlled by oxygen availability and transport limitation in the sediment due to the varying thickness of the oxic zone (Jensen et al ; Gihring et al ; Marchant et al ). Direct methods for the determination of nitrification rates are compromised by the fact that 15 NH 4 + additions increase the NH 4 + pool at low pore‐water NH 4 + concentrations several‐fold, thereby artificially enhancing rates of NH 4 + ‐limited nitrification (Jäntti et al ). Alternatively, isotope dilution approaches with added 15 NO 2 − have been used to quantify nitrification rates (e.g., Jäntti et al ; Marchant et al ).…”
Section: Evolution Of the Whole‐core Iptmentioning
confidence: 99%
“…Direct methods for the determination of nitrification rates are compromised by the fact that 15 NH 4 + additions increase the NH 4 + pool at low pore‐water NH 4 + concentrations several‐fold, thereby artificially enhancing rates of NH 4 + ‐limited nitrification (Jäntti et al ). Alternatively, isotope dilution approaches with added 15 NO 2 − have been used to quantify nitrification rates (e.g., Jäntti et al ; Marchant et al ). Other ways of applying the IPT have also been implemented (e.g., see Steingruber et al ), such as stand‐alone slurries or bag incubations (e.g., Engström et al ; Brandsma et al ) which provide potential rates of NO 3 − ‐reducing processes but cannot be reliably used to reflect in situ rates.…”
Section: Evolution Of the Whole‐core Iptmentioning
confidence: 99%
See 1 more Smart Citation